Managing Relief Inventories Responding to Natural Disasters: Gaps Between Practice and Literature - Ye, Yusen; Jiao, Wen; Yan, Hong (Production and Operations Management, 2020)
In response to highly unpredictable sudden‐onset natural disasters, efficient and effective management of disaster relief inventory (DRI) is essential. This study proposes a simple framework based on three fundamental DRI‐related decision themes, which are (1) who respond to DRI calling, (2) where to locate DRI, and (3) how to control DRI, aiming at identifying the research gaps between the realities’ calling and the literature’s consideration with a focus on DRI management. We review relevant literature for each decision theme, summarize the insights provided by the literature, assess the practical needs and procedures and present our detailed perspectives on the research gaps in practice. The chief implication from our observations and arguments is that scaling up a DRI response for catastrophic disasters and events which prepares the whole community for worst‐case scenarios has been highlighted in academics and practice but lack operational research in the area of relevant decision‐making tactics. Existing research concerning the DRI management issues of various coordination forms of disaster responders, the location‐allocation decision‐making determinants with DRI prepositioning and the DRI control policy in the face of various disaster uncertainties is still far from being fully understood, appropriately characterized and profoundly discussed. We recommend the potential future research areas with the implications of this review in the last conclusion section, wishing to provide researchers a better understanding of the needs in the real‐world.